2004
DOI: 10.1117/12.559969
|View full text |Cite
|
Sign up to set email alerts
|

Theoferometer for high-accuracy optical alignment and metrology

Abstract: The accurate measurement of the orientation of optica l parts and systems is a pressing problem for upcoming space m issions, such as stellar interferometers, requiring the know ledge and maintenance of positions to the sub-arcsecond level. Theodo lites, the devices commonly used to make these measurements, cannot provide the needed level of accuracy. This paper describes the design, construction, and testing of an interferometer system to fill the w idening gap between future requirements and current capabi l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Alignment is one of the key concepts in the process of assembling and testing space equipment [1][2][3][4]. When the final performance of a system is more dependent on the installation angles of the equipment, the importance of alignment increases to the point that it is necessary to extract the installation angles of the equipment with an accuracy of a few seconds of arc or even better.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alignment is one of the key concepts in the process of assembling and testing space equipment [1][2][3][4]. When the final performance of a system is more dependent on the installation angles of the equipment, the importance of alignment increases to the point that it is necessary to extract the installation angles of the equipment with an accuracy of a few seconds of arc or even better.…”
Section: Introductionmentioning
confidence: 99%
“…Various optical methods have been developed by researchers to perform the alignment process [2,5]; Methods based on laser detectors [5], interferometry [6], and theodolite [9] are the three main approaches. The interferometric method is used in the alignment process of parts that require very high installation accuracy; In 2004, Toland and his colleagues showed that using this method, the average measurement error of 0.36 arcsec for the azimuth direction and 0.23 arcsec for the elevation direction can be reached [2]. This method is expensive and difficult to setup, so it is not recommended for applications that do not require such high precision.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Arnold Engineering Development Center offers a test chamber for the verification and evaluation of the space sensors in state-of-the-art missions (Lowry et al, 2005). More examples can be found about test set-up buildings which focus on optical misalignment procedures (Blackwood et al, 1991;Van Veggel et al, 2005;Toland et al, 2004;Leviton et al, 2002). Although it is crucial to prepare such testbeds for state-of-the-art missions, test methods that are less complex and expensive are appreciated for common satellite missions.…”
Section: Introductionmentioning
confidence: 99%